PETROLOGY AND GEOCHEMISTRY OF INTRUSIVE ROCKS FROM THE SOUTH OF NAQADEH, WEST AZERBAIJAN, IRAN - Kordi, Abdollah; Ashja-Ardalan, Afshin; Sheikhzakariayi, Seyed-Jamal; Ashrafi, Nasser (Gênero & Direito, 2019)
The intrusive rocks of Naqadeh are features of Laramide magmatism in the Sanandaj–Sirjan zone. According to petrographic studies, the composition of intrusions consist of acidic, intermediate, and basic rocks. including syenogranites, monzogranite, granodiorites, quartz diorites, quartz monzonites, quartz monzonite, quartz syenite, and olivine gabbro—in order of abundance. Minerals forming intrusive rocks include alkali feldspar (orthoclase and microcline), quartz, plagioclase (andesine to anorthite), amphibole (magnesiohornblende to tschermakite hornblende), pyroxene (diopside), olivine (hyalosiderite to hortonlite), apatite, titanite, zircon, muscovite, and opaque minerals. The chemical analysis of the granitoids revealed their potassium-rich calc-alkaline nature, falling within the meta-alumin to per-alumin range in terms of alumin saturation. Tectonomagmatic diagrams for the studied rocks suggest that they are compatible with granitoids of the continental-subduction zone. Primitive-mantle- and chondrite-normalized spider diagrams indicated no depletion in any elements, exhibiting a negative overall slope which is consistent with subduction patterns (negative Ta, Ti, Zr anomalies, and positive K anomaly). Overall, a review of field observations, mineralogy, geochemistry, and diagrams illustrating the sources of granites showed that the intrusive rocks in the study region are, in fact, I-type granite and that the magmatism is a result of the subduction of the oceanic crust, Neotethys, under the Iranian continental crust.